Project-level Women’s Empowerment in Agriculture Index for Market Inclusion (Pro-WEAI+MI): Malawi Case Study - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The project-level Women’s Empowerment in Agriculture Index for market inclusion (pro-WEAI+MI) is a modified version of the pro-WEAI that captures empowerment across commodity value chains (VC), VC actors, and beneficiaries of VC/training interventions. This dataset from Malawi is one of four country case studies that developed additional market inclusion (+MI) indicators to complement the pro-WEAI. The Malawi case study was conducted as part of the Agricultural Technical Vocational Education and Training for Women (ATVET4W) Program, a gender-sensitive approach to technical training and market linkages in priority agricultural value chains led by the African Union Development Agency-New Partnership for Africa’s Development (AUDA-NEPAD) and Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). To compare program beneficiaries versus non-beneficiaries, a household survey was collected from September to October 2019 in five districts where ATVET4W has (1) started some activities, (2) shown initial commitment from a community college, and (3) shown a high likelihood to continue with the program. These districts cover different regions (North, Central, South), agroecological zones, and socioeconomic profiles. This data package includes the pro-WEAI+MI questions implemented in Malawi, basic household and demographic information, and constructed pro-WEAI and +MI indicators.